PENGARUH MANAJEMEN LABA (EARNING MANAGEMENT) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hasni Yusrianti; Abdi Satria (JEMBATAN, 2014)
This study purposed to analyze the effect of earning management on return of share in go public manufacturing companies in Indonesian Stock Exchange with the research period from 2008 until 2012. Sample of this study were 40 manufacturing companies from 137 population that listed in Indonesian Stock Exchange. Data was collected by using purposive sampling method with specified criteria. The analysis uses descriptive statistic and hypothesis test uses linier regression and T test with 5% level significance, and also uses test of determination correlation coefficient (r2). Earning management was measured by discretionary accruals. The result shows that earnings management has F count 3.087 with significance 0,080, so it is more than 0.05. Furthermore, coefficient of determination (R2) is 0,015 or 1,5%. This research conclusion is there is no significant influence between earning management on return of shares in the manufacturing companies. This indicates that the size of the earnings management conducted by the company's management does not have a significant effect to rising company return of share manufacturing companies in Indonesian Stock Exchange.Keyword : Earning Management, Return of Share, Indonesia Stock Exchange